Identification of circRNAs in the Liver of Whitespotted Bamboo Shark (Chiloscyllium plagiosum) - Zhang, Wenjie; Qin, Ping; Gong, Xiaoxia; Huang, Lei; Wang, Chan; Chen, Guiqian; Chen, Jianqing; Wang, Lei; Lv, Zhengbing (Frontiers in Genetics, 2020)
Whitespotted bamboo shark (Chiloscyllium plagiosum), a member of the cartilaginous fish family, has an extremely large liver and demonstrates a strong regeneration ability and immune regulation. Circular RNAs (circRNAs), an important class of non-coding RNAs, Increasing evidence suggests that circRNAs are a kind of potential regulators, Recently, researchers have isolated and identified different circRNAs from various species, but reports on the circRNAs of C. plagiosum are few. This study , we have identified a total of 4558 circRNAs in the liver of C. plagiosum. This finding suggests that circRNAs are not evenly distributed in the chromosomes and follow the GT-AG rule during cyclization. Alternative back-splicing might exist in shark circRNAs as shown by the authenticity identification of predicted circRNAs. The binding strength of circRNAs (< 2000 bp) and the detected miRNAs in shark liver were simultaneously analyzed to construct an mRNA–miRNA–circRNA network for the Glutathione S-transferase P1 gene, and circRNA authenticity was verified.Our data not only provide novel insights into the rich existence of circRNAs in marine animals, but the identified circRNAs in the liver of C. plagiosum also provide a basis for characterizing their functions in liver homeostasis.